Developing and Verifying A 3.5ghz Smart Antenna for Wideband 5G Communication - Tian Teck, Chia; Al-Fadhali, Najib; Majid, Huda; Jumadi ,; Shairi, Azwan; M. Gisamalla, Mohammed S.; Ashyap, Adel; Mukred, Jamil; Abo Mosali, Najmaddin (Journal of Advanced Industrial Technology and Application, 2023)
Nowadays, 5G technology plays a crucial role in various aspects of human life, such as communication, business, education, and transportation. The 5G technology utilizes frequency bandwidths that can be categorized into low, medium, and high bandwidths. This study aims to design a 3.5GHz smart antenna using FR-4 substrate and microstrip feeding line for wideband 5G communication in large open areas. The designed antenna is suitable for 5G applications in the 3.5GHz frequency range. The output of the fabrication is measured using a Vector Network Analyzer, which is connected to the microstrip feeding line through a subminiature version A connector. The FR-4 substrate used in this project has a dimension of 40mm x 32mm and a thickness of 1.6mm. Initially, the antenna is simulated using CST software, and then it is fabricated for measurement to validate the simulation result. The simulation result shows a return loss of -42.287dB and a VSWR of 1.016, which is approximately equal to 1.00 of the VSWR